Biochemical assessment university collections bean (Eurasian Journal of Ecology, 2016)
This article concern the investigation of biochemical parameters of university collections of beans grown in the prairie and foothill areas of Almaty region. The amino acid composition of the seeds, as well as the qualitative and quantitative composition of fatty acids were determine.
Keywords: beans; grade samples; biochemical evaluation; amino acid composition; fatty acid composition